Analysis of contextual variables in the evaluation of child abuse in the pediatric emergency setting - Ana Nunes de Almeida; Vasco Ramos; Helena Nunes de Almeida; Carlos Gil Escobar; Catarina Garcia (Brazilian Society of Pediatrics, 2017)
Objective: This article comprises a sample of abuse modalities observed in a pediatric emergency room (PER) of a public hospital in the Lisbon metropolitan area and a multifactorial characterization of physical and sexual violence. The objectives are: (1) to discuss the importance of social and family variables in the configuration of both types of violence; (2) to show how physical and sexual violence have subtypes and internal diversity. Methods: A statistical analysis was carried out in a database (1063 records of child abuse between 2004 and 2013). A form was applied to cases with suspected abuse, containing data on the child, family, abuse episode, abuser, medical history, and clinical observation. A factorial analysis of multiple correspondence was performed to identify patterns of association between social variables and physical and sexual violence, as well as their internal diversity. Results: The prevalence of abuse in this PER was 0.6%. Physical violence predominated (69.4%), followed by sexual violence (39.3%). Exploratory profiles of these types of violence were constructed. Regarding physical violence, the gender of the abuser was the first differentiating dimension; the victim's gender and age range were the second one. In the case of sexual violence, the age of the abuser and co‐residence with him/her comprised the first dimension; the victim's age and gender comprised the second dimension. Conclusion: Patterns of association between victims, family contexts, and abusers were identified. It is necessary to alert clinicians about the importance of social variables in the multiple facets of child abuse.